Simply lies - Baldacci, David (GCP, Grand Central, 2023)
Mickey Gibson, single mother and former detective, leads a hectic life: juggling the demands of her two small children with the tasks of her job working remotely for ProEye, a global investigation company that hunts down wealthy tax and credit cheats. When Mickey gets a call from a colleague named Arlene Robinson, she thinks nothing of Arlene's unusual request for her to go inventory the vacant home of an arms dealer who cheated ProEye's clients and fled. That is, until she arrives at the mansion to discover a dead body in a secret room--and that nothing is as it seems. Not only does the arms dealer not exist but the murder victim turns out to be Harry Langhorne, a man with mob ties who used to be in Witness Protection. What's more, no one named Arlene Robinson works at ProEye.